Digital Marketing and Product Quality as Drivers of Purchase Decisions Evidence from CV. Alfa Galuh Perkasa, a Safety Equipment SME in Bandung - Mahendra, Allana Veda; Pratminingsih, Sri Astuti (Yayasan Sinergi Kawula Muda, 2025)
This study explores how product quality and digital marketing influence consumer purchase decisions within the niche sector of fire safety equipment, using CV. Alfa Galuh Perkasa, a small and medium-sized enterprise (SME) based in Bandung, Indonesia, as a case study. In the wake of the COVID-19 pandemic, consumer behavior has become increasingly digital, yet limited empirical research addresses how safety product distributors are adapting to this shift. The study seeks to answer the extent to which product quality and digital marketing impact consumer purchasing decisions in this industry. The novelty of this research lies in its dual-variable focus—product quality and digital marketing—applied to a sector where digital engagement is still in its formative stages, contrasting with the more commonly studied fast-moving consumer goods. A quantitative approach was adopted, utilizing a cross-sectional design. Data were collected through an online survey completed by 105 respondents, selected via accidental sampling. Multiple linear regression analysis using SPSS was employed to assess the influence of the independent variables on purchasing decisions. The results demonstrate that both product quality and digital marketing significantly and positively affect consumer purchasing decisions. Notably, product performance and reliability emerged as key factors, while digital visibility—especially through search engines and affiliate marketing—proved to be critical in shaping consumer awareness and interest. The findings suggest that SMEs in niche industries can enhance customer engagement and drive purchasing behavior by improving product reliability and strategically expanding their digital marketing channels. This study provides actionable insights for businesses aiming to stay competitive in an increasingly digital market landscape.